2024
DOI: 10.1007/s00438-024-02097-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of missing data on evolutionary analysis of sequence capture bycatch, with application to an agricultural pest

Leo A. Featherstone,
Angela McGaughran

Abstract: Sequence capture is a genomic technique that selectively enriches target sequences before high throughput next-generation sequencing, to generate specific sequences of interest. Off-target or ‘bycatch’ data are often discarded from capture experiments, but can be leveraged to address evolutionary questions under some circumstances. Here, we investigated the effects of missing data on a variety of evolutionary analyses using bycatch from an exon capture experiment on the global pest moth, Helicoverpa armigera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…However, some empirical evidence has demonstrated that allowing for substantial missing data recovers a higher number of loci, and thus more power for population assignment inference than a more conservative approach (Chattopadhyay et al., 2014 ). Also, different data completion levels showed little impact on most genetic summary statistics (Shafer et al., 2017 ) and on the identity of genetic groups or subspecies recovered (our study, Featherstone & McGaughran, 2024 ). Hodel et al.…”
Section: Discussionmentioning
confidence: 48%
“…However, some empirical evidence has demonstrated that allowing for substantial missing data recovers a higher number of loci, and thus more power for population assignment inference than a more conservative approach (Chattopadhyay et al., 2014 ). Also, different data completion levels showed little impact on most genetic summary statistics (Shafer et al., 2017 ) and on the identity of genetic groups or subspecies recovered (our study, Featherstone & McGaughran, 2024 ). Hodel et al.…”
Section: Discussionmentioning
confidence: 48%